Collagen-specific cytotoxic T lymphocyte responses in patients with ankylosing spondylitis and reactive arthritis. - Gao, X; Wordsworth, P; McMichael, A (1994)
Both ankylosing spondylitis (AS) and reactive arthritis (ReA) are strongly associated with HLA-B27 although the mechanism for this association is still unknown. Here we examine the hypothesis that B27-restricted, joint antigen-specific cytotoxic T lymphocytes (CTL) may be the driving force of AS and ReA. Type II and type XI procollagens (CII and CXI, respectively), expressed almost exclusively in the articular cartilage of the joints, were chosen as the possible targets of autoimmune CTL. Type I procollagen (CI), expressed in many different tissues, was also included as control. Nineteen nonamer peptides bearing appropriate HLA-B27 binding motifs from human CI, CII and CXI were identified and synthesized. When analyzed for binding affinity to HLA-B27 in assembly assays, four (two from CII, two from CXI) were found capable of binding to HLA-B27 with high affinity. These B27-binding collagen peptides were then used to stimulate peripheral blood lymphocytes from eight B27-positive AS and three ReA patients for identification of possible B27-restricted autoimmune CTL. HLA-B27-restricted CTL specific for one of the CII peptides, P109 were found in one of the ReA patients, but in none of the others.